Security of a key agreement protocol based on chaotic maps - Han, Song (Elsevier, 2008)
Kacorev et al. proposed new public key encryption scheme using chaotic maps. Subsequently, Bergamo et al. has broken Kacorev and Tasev?s encryption scheme and then applied the attack on a key agreement protocol based on Kacorev et al.?s system. In order to address Bergamo et al.? attack, Xiao et al. proposed a novel key agreement protocol. In this paper, we will present two attacks on Xiao et al.?s key agreement protocol using chaotic maps. Our new attack method is different from the one that Bergamo et al. developed. The proposed attacks work in a way that an adversary can prevent the user and the server from establishing a shared session key even though the adversary cannot get any private information from the user and the server?s communications.